(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
In recent years, 3D printing technology has revolutionized radiological applications, offering unprecedented opportunities for patient care, surgical planning, education, and research. This article provides an overview of the innovations in 3D printing technology and its diverse applications in radiology. It explores the creation of patient-specific anatomical models for surgical planning, the development of customized surgical guides and implants, and the integration of 3D-printed models into medical education and training. Additionally, it discusses current research trends, regulatory considerations, and challenges facing widespread adoption.